IMPLEMENTASI METODE DDD-E PADA PENGEMBANGAN APLIKASI MEDIA PEMBELAJARAN INTERAKTIF IPAS MATERI LAPISAN BUMI - Aziz, Riyan Abdul (JURNAL REKAYASA INFORMASI, 2025)
Interactive learning media can be one solution for teachers to improve student learning outcomes in certain subjects. One of the subjects that requires visualization in the form of images or videos is the material on the layers of the Earth in the fields of natural sciences. This study aims to identify the problems experienced in developing interactive learning media applications for the material on the layers of the Earth in the fields of science and natural sciences. The development method used to create interactive learning media applications for the material on the layers of the earth in the fields of science and natural sciences is DDD-E (Decide, Design, Develop, Evaluate). Interactive learning media has been successfully created, with four main menus: the competency menu, material menu, practice question menu, and game menu. The results of the media expert test using black box testing showed that all menus, features, and buttons functioned properly. The posttest results showed that seventeen students passed above the KKM, the average class score increased to 83 from the previous 56.3.